Probiotic membrane vesicles ameliorate atherosclerotic plaques by promoting lipid efflux and polarization of foamy macrophages - Boping Jing; Yu Gao; Lufang Wang; Feng Guo; Dawei Jiang; Saimei Qin; Mengrong He; Ying Bai; Rui An; Mingxing Xie; Li Zhang (Journal of Nanobiotechnology)
Abstract Foamy macrophages are pivotal contributors to the development and progression of atherosclerotic plaques, posing a substantial threat to human health. Presently, there is no pharmaceutical intervention available to effectively eliminate foamy macrophages. In this study, we demonstrate that probiotic membrane vesicles (MVs) can induce atherosclerotic plaque regression by modulating foamy macrophages. MVs isolated from Lactobacillus rhamnosus exhibited a specific uptake by foamy macrophages. Near-infrared fluorescence (NIRF) imaging, aortic oil red O staining, and hematoxylin and eosin staining showed reductions in the plaque area following MVs treatment. Mechanistically, bioinformatics analysis provided insights into how MVs exert their effects, revealing that they promote lipid efflux and macrophage polarization. Notably, MVs treatment upregulated NR1H3, which in turn increased ABCA1 expression, facilitating lipid efflux from foamy macrophages. Moreover, MVs shifted macrophage polarization from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype, highlighting their potential to create a more protective environment against plaque progression. This study is significant as it introduces MVs as a novel therapeutic platform for the targeted delivery of anti-inflammatory agents to atherosclerotic sites. By specifically modulating macrophage function, MVs hold considerable potential for the treatment of atherosclerosis and related cardiovascular diseases, addressing an unmet need in current therapeutic strategies.